Evasion of I Interferon-Mediated Innate Immunity by Pseudorabies Virus - Zhang, Rui; Tang, Jun (Frontiers in Microbiology, 2021)
Type I interferon (IFN-I) mediated innate immunity serves as the first line of host defense against viral infection, ranging from IFN-I production upon viral detection, IFN-I triggered signaling pathway that induces antiviral gene transcription the antiviral effects of IFN-I induced gene products. During coevolution, herpesviruses have developed multiple countermeasures to inhibit the various steps involved to evade the IFN response. This mini-review focuses on the strategies used by the alphaherpesvirus Pseudorabies virus (PRV) to antagonize IFN-I mediated innate immunity, with a particular emphasis on the mechanisms inhibiting IFN-I induced gene transcription through the JAK-STAT pathway. The knowledge obtained from PRV enriches the current understanding of the alphaherpesviral immune evasion mechanisms and provides insight into the vaccine development for PRV control.